Analysis Of Financial Performance On Stock Prices With Earning Growth As A Mediator Variable On Infrastructure In Indonesia - Wahyuni, Iis; Herawati, Heti; Suharmiati, Suharmiati; Salim, Inne Natalia (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
Financial performance is one of the indicators used by investors to assess a company. The stock price is a reference used in investing. This study aims to analyze the effect of the company's financial performance proxied by Return On Equity (ROE), Net Profit Margin (NPM) and Total Asset Turnover (TATO) on Stock Price with Earning Growth as a mediator variable. This research uses a quantitative approach. The data used is secondary data obtained through the Indonesia Stock Exchange on the website www.idx.co.id. The population in this study were 16 infrastructure sector companies listed on the Indonesia Stock Exchange from 2019 to 2023. Purposive sampling is used as a method in selecting samples. So that from the predetermined criteria, 80 units of analysis were obtained. In this study, path analysis techniques were used. Hypothesis testing was carried out using the Eviews 12 program. Stock prices are valued at closing prices. The results of this study indicate that Return On Equity (ROE), Net Profit Margin (NPM) and Total Asset Turnover (TATO) have no effect on Earning Growth . Return On Equity (ROE), Net Profit Margin (NPM), Total Asset Turnover (TATO) and Earning Growth have no effect on stock prices. For the mediation effect, it results that Earning Growth is unable to mediate the effect of Return On Equity (ROE), Net Profit Margin (NPM) and Total Asset Turnover (TATO) on stock prices.   Keywords: Financial Performance, Stock Price, Return On Equity, Net Profit Margin, Total Asset Turnover, Earning Growth.